TREN PENGEMBANGAN PROGRAM MAGISTER KOMUNIKASI DAN PENYIARAN ISLAM DALAM TRANSFORMASI IAIN MENJADI UIN SURAKARTA - Kamila Adnani (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2019)
The transformation of The State Institute for Islamic Studies (IAIN) towards State Islamic University (UIN) Surakarta is understood as a strategic step to improve the quality of the institution's education. IAIN Surakarta needs to fix several factors, both internal and external, in order to maintain its existence as a public institution in the implementation of Islamic Higher Education. The dilemma faced in the transformation of IAIN towards UIN is the dualism-dichotomic phenomenon of science developed. The research method used is descriptive qualitative. This research was conducted from June 14, 2017 to September 12, 2017. The data was collected through observation, interviews, and documentation. The data were analyzed by descriptive analysis with inductive thinking methods. Based on the results of the study, it was concluded that: 1) Surakarta IAIN needs to develop general study programs as well as integration between general science and Islam, including KPI Study Programs; 2) the development of study programs at IAIN Surakarta is important in order to accelerate the transformation into UIN Surakarta; 2) the rapid trend of media development needs to be addressed by the Surakarta IAIN.